Influence of Marketing Strategies on Business Performance of Selected Small and Medium Enterprises in Abeokuta Metropolis, Ogun State, Nigeria (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Marketing strategy is a substantial driving force that differentiates the success of many businesses by conceptualizing and implementing a good marketing strategy with clear demarcation. This study investigates the relationship between marketing strategies and business performance, evidence from Abeokuta metropolis. The study conceptualized a model showing the relationship among product strategy, promotional strategy, pricing strategy and business performance. This study used descriptive and inferential survey research approach. The study population was the selected SMEs owners in Abeokuta metropolis, Ogun state. Data was collected from 158 respondents through a validated and reliable questionnaire. One hundred and fifty-eight (158) copies of the questionnaire were successfully retrieved and were analyzed using descriptive and inferential statistics. The findings reveal a significant positive relationship between product strategy and business performance (PC = 0.32, N = 158, p < 0.01); No significant relationship between promotional strategy and business performance (PC = 0.28, N = 158, p < 0.05); a significant positive relationship between pricing strategy and business performance (PC = 0.30, N = 158, p < 0.03); The findings also reveal that these variables (product strategy, promotional strategy and pricing strategy collectively have significant impact on business performance. Conclusively, the finding of the study shows that product strategy, promotional strategy, and pricing strategy significantly enhance business performance among SMEs in the Abeokuta metropolis. The study recommends that SME owners should use the AIDA framework to create marketing campaigns that build awareness, generate interest, foster desire, and prompt action.